Advances in otolith-related protein research - Huang, Shouju; Qian, Shuxia (Frontiers in Neuroscience, 2022)
Otoliths are biological crystals formed by a layer of calcium carbonate crystal that adhere to the ciliary surface of the utricular and saccular receptors in the vestibule of the human inner ear, enabling the utricle and saccule to better perceive the changes in linear and gravitational acceleration. However, the molecular etiology of otolith related diseases is still unclear. In this review, we have summarized the recent findings and provided an overview of the proteins that play important roles in otolith formation and maintenance (Otoconin-90, Otolin-1, Otolith Matrix Protein-1, Cochlin, Otogelin, α-Tectorin,β-Tectorin, Otopetrin-1 and Otopetrin-2, PMCA2, etc.), etc.), providing new insight for the prevention and management of benign paroxysmal positional vertigo (BPPV) with basis for otolith-related proteins as potential biomarkers of vestibular disease.